Evaluation of Water Quality and Sustainability of Treated Wastewater for Irrigation and the Municipal Uses in Karbala Province - Haneen Hussain Abbas; Saad Wali Alwan (Kufa Journal for Agricultural Sciences)
This study was conducted to assess the quality of treated wastewater from the wastewater treatment project in Karbala. and its reuse for irrigation and municipal by Canadian Water Quality Index (CWQI). Samples were collected periodically with three replications from (Dec. 2021 –Jul.2022). The results showed that the water was characterized by high salinity, TDS, TSS, total hardness, EC, and turbidity, which were recorded at 2039 -3739 mg/l; 1030-2640; 30-48 mg.L-1. 3740 -2040 µs/cm and 3.17 -8.5 NTU respectively, major cations and anions (Cl-, PO4-3, NO3-, S2O4-2 and K+) exceed significantly to (57-380; 0.003-4.99; 8.63-44.25; 453-1340; 4.537) mg. L-1,  sodicity index (SAR, Na+ and Sodium percentage ratio) and magnesium hazard, were detected 0.59 – 4.89; 138-447.5 12.98-43.76), Water can be classed depending on that as a permit to good. However, it’s categorized as marginal-fair according to the CCME Water quality index, especially in the far station from the plant water. Principal Component Analysis (PCA) showed depending on its effect on the value of the index, where the first group PCA1 recorded the largest proportion (35.26%) and includes dissolved solids, EC, salinity, Na, SAR, Na%, alkalinity, SO4, pH, DO, BOD5 Mg risk of magnesium. The second group, PCA2, with the lowest percentage (18.78%), was represented by temperature, Ca+2, total hardness, K, Cl, PO4, NO3, TSS, and turbidity. This water is a wealth that can be exploited in the cultivation of the desert adjacent to Karbala governorate, and by adopting different methods to reduce the effect of salinity.